(untitled) (Journal of Economic Research & Business Administration, 2015)
Kazakhstan’s main priorities for entering the group of 30 world’s most developed countries are: updating and strengthening the innovative trend of industrialization, improving agriculture sector, the creating knowledge-based economy, developing infrastructure, supporting small and middle enterprises (SME). This article deals with the problems of implementation of the program and presents the suggestions of overcoming them